Rice growth performance, nutrient use efficiency and changes in soil properties influenced by biochar under alternate wetting and drying irrigation - Haque, Ahmad Numery Ashfaqul; Uddin, Md. Kamal; Sulaiman, Muhammad Firdaus; Mohd Amin, Adibah; Hossain, Mahmud; Solaiman, Zakaria M.; Mosharrof, Mehnaz (Mary Ann Liebert, 2022)
Water-saving irrigation occasionally causes an inconsequential yield loss in rice; thereby, biochar incorporation in this context has great scope due to its properties, including the release of nutrients and improving soil physicochemical properties. An experiment was conducted to investigate the effect of biochar combined with fertilizer on physiological response, water and nutrient efficiency of rice and changes in biochemical properties of soil under AWD (alternate wetting and drying) irrigation system. Two types of irrigation practice, such as AWD and CF (continuous flooding), and four types of fertilizer combination, namely T1: 25% Rice husk biochar (RHB) + 75% of recommended fertilizer dose (RFD); T2: 25% oil palm empty fruit bunch biochar (EFBB) + 75% of RFD; T3: 100% RFD; and T0: 0% biochar and fertilizer, were assigned to assess their impacts. The AWD irrigation produced a sharply reduced grain yield (210.58 g pot−1) compared to CF irrigation (218.04 g pot−1), whereas the biochar combination treatments T1 and T2 produced greater yields (260.27 and 252.12 g pot−1, respectively), which were up to 12.5% higher than RFD. Within AWD, irrigation water usage by T1 and T2 (98.50 and 102.37 g L−1, respectively) was profoundly reduced by up to 28.8%, with improved water use efficiency (WUE). The main effect of biochar treatment T1 and T2 also increased photosynthesis rate during vegetative and maturing stage (up to 17.6 and 24.4%, respectively), in addition to boosting agronomic efficiency of nitrogen (N), phosphorous (P) and potassium (K) compared to RFD (T3). Nevertheless, T1 and T2 significantly enhanced the total carbon and nitrogen; dehydrogenase and urease enzyme activities also increased in both irrigation regimes. The results reveal that the integrated application of RHB and EFBB with fertilizer in the AWD regime significantly reduces irrigation water usage and improves nutrient use efficiency, WUE and soil biochemical properties with a minimum yield penalty for rice.